The Appalbees menu: a multiyear, multilocus metagenetic assessment of pollen foraging by Appalachian Bombus affinis workers - Cornman, Robert S.; Hepner, Mark J.; Otto, Clint R.V. (PeerJ, 2026)
Background Detailed studies of foraging behavior are needed for scientific management of the endangered rusty-patched bumblebee (Bombus affinis) in the disjunct and ecologically differentiated habitats it presently occupies. Current knowledge gaps hinder recovery planning but are challenging to redress through direct observation of rare interactions in the field. Methods We used genetic metabarcoding to characterize the taxonomic composition of pollen collected by B. affinis workers in the Appalachian mountains of Virginia and West Virginia from 2021–2023. We developed a custom sequence database of the regional flora and compared results for two independent genetic loci, internal transcribed spacer 1 and internal transcribed spacer 2 (ITS1 and ITS2). Results While ITS2 consistently detected more plant diversity, results from the two loci were broadly concordant with a few notable exceptions. The plant genera Hydrangea, Actaea, Rhododendron, Tilia, and (unexpectedly) Laportea were prominent in midsummer samples, with Rubus a consistent contributor in late spring and early summer. Pea flowers (family Fabaceae) were relatively infrequent but the genera Securigera and Trifolium were detected before the Hydrangea bloom and again in late summer afterwards. The diversity of forage plants was highest in late summer, driven primarily by various genera of Asteraceae. Comparing the current data with previous work indicates regional differentiation in forage plants between Appalachia and the upper Midwest, but also allows ‘consensus’ forage sources that are supported by multiple lines of evidence and shared between regions to be tabulated. These results should help managers focus survey efforts for this endangered species and plan habitat enhancements.
Keywords: Pollen metabarcoding; Bombus affinis; Rusty-patched bumblebee; Plant-insect interactions; Pollination; Biomonitoring